CRITICAL URBAN PEDAGOGY: Convites as Sites of Southern Urbanism, Solidarity Construction and Urban Learning. (29th August 2022) - Ortiz, Catalina; Millan, Gynna
Abstract: Learning from the pedagogical potentials of Southern city‐making practices is imperative to foster emancipatory urban learning settings. However, the ways in which urban learning spaces beyond professional settings operate and how Southern urbanism practices constitute new critical pedagogies are poorly understood. We draw on research about urban learning on 'slum upgrading' in the city of Medellín (Colombia), a benchmark in dealing in tandem with informality and urban violence, to analyze the pedagogical potentials of convites . Convites are an essential sociospatial mechanism of self‐build settlements rooted in solidarity networks that initiate collective action and celebration through public cooking. This practice of makeshift community kitchens led by women became the backbone of the response to the scarcities caused by the pandemic in self‐built neighborhoods in Latin America. In this article we ask what Southern urbanism and critical pedagogy can learn from convites . We then analyze the ways in which convites combine community kitchens as learning environments, the use of collective storytelling as a learning device, and collective action through networked solidarities. We argue that critical urban pedagogy is a situated pedagogy derived from everyday relations of place, body and materiality infused by memory and articulated by storytelling.